Long-Term Observation of Coexistence of Posterior Polymorphous Corneal Dystrophy, Resultant High Myopia and Nonkeratoconic Developing Corneal Astigmatism: A Case Report of 7-Year Tracking in a Chinese Boy - Shen, Jianqin (Medicine (Baltimore), 2015)
Posterior polymorphous corneal dystrophy (PPCD) is an extremely rare, bilateral, and inherited disorder, which affects the corneal endothelium and Descemet's membrane. Few PPCD cases in Chinese patients have been published so far. As far as we know, there are few studies which focused on the associations between PPCD and high myopia either. Here we report a rare case of coexistence of posterior polymorphous corneal dystrophy, resultant high myopia and with-the-rule developing corneal astigmatism in a young Chinese boy. A 6-year-old boy was first referred to our department 7 years ago, complaining of bilateral poor vision. Examinations of both eyes including ophthalmologic examination, cycloplegic refraction examination, confocal microscopy findings, and corneal topography were performed. Bilateral small aggregates of vesicular lesions and patchy hyperreflectivity were observed at the level of the Descemet's membrane on confocal microscopy, which is consistent with typical PPCD. Optometry and corneal topography examinations showed a resultant high myopia. Ocular examinations were performed annually to follow up with the patient in the past 7 years. The corneal lesions remained stable whereas an axial elongation and a sharp increase in both spherical and cylindrical equivalent power were observed. Close follow-ups including thorough scrutiny of the endothelium and systematic ocular ancillary examinations are essential for patients with PPCD. The pathological coexistence of PPCD and high myopia in our case is possibly due to a shared etiological pathway or genetic background. Advanced genetic analysis on similar cases is expected if more samples can be provided.